Finding the key elements that enhance the Procurement process - Case Woima corporation - Nykänen, Elli (My University, 2019)
Procurement has changed over the years and has become a key element in today’s business. Supply chain management and procurement are key business drivers to companies. The changes in business has developed new requirements and the challenge for companies is that how they can adjust their process to meet these new requirements. What truly are the elements that makes a company's procurement process the most effective? This can be studied through the element of maturity the purchasing process has. In this study, the Procurement Competitive Capability Maturity is reviewed. Through the maturity model the key elements that enhance the purchasing process are tried to find. The study also examines the effect of what e-technology solutions can have on procurement and how they can possibly be an advantage or disadvantage for the process. This is a case study that applies both exploratory and inductive approach. In this study, the empirical part was conducted by utilizing semi-structured interviews for persons working in the field of supply chain management. The interviews were then analyzed in order to conduct the final results of this study. This study also examines the current literature found in the field of supply chain management and compares findings from the interviews to the literature. The research has indicated that the procurement process is a complex and multidimensional process. Procurement has a lot of moving parts that can affect the whole supply chain. What was found that a lot of communication and co-operation is needed with suppliers and that was the most important element when it came to procurement. The need for good supplier network was also highlighted. The study also showed that time management is also important when it comes to procurement. The communication inside own organization is also an important part of the procurement process. Furthermore, this study offers some insights for the case company on which they should focus on while of developing their own procurement process to achieve their goals regarding to effectiveness
Keywords: Maturity model; Supply chain management; Procurement; Purchasing; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|